МОНІТОРИНГ ЕФЕКТИВНОСТІ РОБОТИ В ЛОКАЛЬНИХ ЕЛЕКТРОЕНЕРГЕТИЧНИХ СИСТЕМАХ - С.П. Денисюк; Г.С. Бєлоха; К.М. Гілевич; І.С. Чернещук (Праці Інституту електродинаміки Національної академії наук України)
The local electricity system is a decentralized grid, one of the tasks of which is the optimized management of distributed energy resources. To achieve effective integration and interaction in the work of local systems at the level of residential and commercial buildings, a set of systems and algorithms that are combined into monitoring systems is required. A transactive energy system allows multiple interconnected buildings to exchange energy for greater energy efficiency. The article presents the peculiarities of monitoring such systems, the method of assessing the efficiency of the local sys-tem and the assessment of the unevenness of the energy consumption schedules when powering the elements of the local system. The introduction of modern programs (mechanisms) of demand side management to participate in the balanc-ing of supply and demand is considered. The application of demand management mechanisms for a local system with non-intrusive load monitoring and an energy management system based on transactive energy approaches and methods is considered. Bibl 14, fig. 2.